Seawater cultivation of freshwater cyanobacterium Synechocystis sp. PCC 6803 drastically alters amino acid composition and glycogen metabolism - Iijima, Hiroko; Nakaya, Yuka; Kuwahara, Ayuko; Hirai, Masami Yokota; Osanai, Takashi (Frontiers in Microbiology, 2015)
Water use assessment is important for bioproduction using cyanobacteria. For eco-friendly reasons, seawater should preferably be used for cyanobacteria cultivation instead of freshwater. In this study, we demonstrated that the freshwater unicellular cyanobacterium Synechocystis sp. PCC 6803 could be grown in a medium based on seawater. The Synechocystis wild-type strain grew well in an artificial seawater (ASW) medium supplemented with nitrogen and phosphorus sources. The addition of HEPES buffer improved cell growth overall, although the growth in ASW medium was inferior to that in the synthetic BG-11 medium. The levels of proteins involved in sugar metabolism changed depending on the culture conditions. The biosynthesis of several amino acids including aspartate, glutamine, glycine, proline, ornithine, and lysine, was highly up-regulated by cultivation in ASW. Two types of natural seawater (NSW) were also made available for the cultivation of Synechocystis cells, with supplementation of both nitrogen and phosphorus sources. These results revealed the potential use of seawater for the cultivation of freshwater cyanobacteria, which would help to reduce freshwater consumption during biorefinery using cyanobacteria.